Pentingnya Kualitas Pelayanan dan Kepercayaan Konsumen Terhadap Loyalitas Pelanggan di CV Putra Timur Farm - Rama Yudana; Choerul Umam; Tri Esti Rahayuningtyas; Widyatmoko (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
In the constantly shifting and challenging market landscape, one notable phenomenon is the surge in new businesses. This study focuses on examining the impact of service quality and consumer trust on customer loyalty at CV Putra Timur Farm. In the commodity business, where prices frequently fluctuate, maintaining customer loyalty is essential for business sustainability. Data for this research was collected through observations and questionnaires and analyzed using the Structural Equation Modeling (SEM) Partial Least Squares (PLS) method. The results of the analysis indicate that excellent service quality and high levels of consumer trust have a positive and significant effect on customer loyalty. The findings highlight the critical importance of improving service quality and building strong consumer trust to maintain and enhance customer loyalty, especially amid unpredictable price fluctuations in commodity markets. This research underscores the need for businesses to focus on service excellence and trust-building strategies to ensure long-term customer retention and overall business success